Museums & Social Issues : A Journal of Reflective Discourse. (New York City : Routledge, 2006)
Museums & Social Issues is a leading forum for critical conversations on the role of museums in society. Responding to the dense entanglement of museums with every aspect of social, cultural, political and economic life, the journal welcomes original articles, commentaries and reviews that situate museums as vital interlocutors in many of the most urgent debates of our time, from racial justice and post-truth politics to inequality and climate action. (www.tandfonline.com)
Engels
Tijdschriften
Keywords: museumbeleid; sociale geschiedenis